Your Florida Dooryard Citrus Guide - Selecting A Citrus Tree for Your Climate - James J. Ferguson (EDIS)
This document is HS 885, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Originally printed in hardcopy, 1995. Publication date: August, 2002.